Fatigue behavior, failure mode, and stress distribution of occlusal veneers: influence of the prosthetic preparation cusp inclinations and the type of restorative material - Velho, Helder Callegaro (2023)
Objective: To evaluate the effects of cusp inclination of the prosthetic preparation’s occlusal surface and type of restorative material on the fatigue behavior, failure mode, and stress distribution of occlusal veneers. Materials and methods: Glass fiber–reinforced epoxy resin prosthetic preparations for occlusal veneers with three different occlusal surface cusp inclination degrees (0°, 15°, and 30°) were produced and assigned into six testing groups (n = 11) according to the cusp inclination (0°, 15°, or 30°) and type of restorative material (lithium disilicate—LD or resin composite—RC). Despite different substrate preparation cusp inclination degrees, the restorations were designed maintaining 30° inclination between the cusps at the occlusal surface and a thickness of 0.7 mm at the central groove region of the restorations to be machined in a CAD/CAM system. After cementation, the specimens were stored for about 7 days (under water at 37 °C), and subsequently submitted to a load to failure test (n = 2) and an intermittent cyclic fatigue test (n = 9) (initial load: 100 N; step size: 50 N; cycles/step: 10,000; loading frequency: 20 Hz; loading piston: 6-mm-diameter stainless steel) until observing cracks. The data were analyzed by two-way ANOVA, Kaplan–Meier, and Mantel-Cox post hoc tests. Finite element analysis (FEA) and fractographic analyses were performed. Results: The fatigue performance of LD and RC occlusal veneers was evaluated based on different prosthetic preparation cusp inclinations. The 0° inclination showed the best fatigue performance for both materials (LD: 944N, RC: 861N), while the 15° and 30° inclinations had lower values (LD: 800N and 533N, RC: 739N and 717N, respectively). The study also found that for a 0° inclination, LD occlusal veneers performed better than RC ones (LD: 944 N > RC: 861N), while for a 30° inclination, RC occlusal veneers had better fatigue performance than LD ones (LD: 533N < RC: 717N). No significant difference was observed between the materials for a 15° inclination (LD: 800N = RC: 739N). The FEA results showed a higher tensile stress concentration on lithium disilicate than on resin composite occlusal veneers. All lithium disilicate occlusal veneers showed radial crack failures, while resin composite occlusal veneers showed Hertzian cone cracks and radial cracks combined. Conclusion: Considering mechanical perspective only, RC occlusal veneers should be indicated when prosthetic preparation cusps inclinations are 30°. When 0° prosthetic preparation cusps inclinations are observed, LD occlusal veneers will behave mechanically better. When a 15° cusp inclination is preserved, both restorative materials behave similarly.